Keragaan Produksi Ayam Broiler Pada Berbagai Metode Pemberian Pakan dan Tipe Lantai Kandang - I Nyoman Sukartha Jaya; Ni Ketut Dewi Haryani; Asnawi Asnawi (LPPM Universitas Mataram, 2018)
The aim of this study was to determine the effect of the restriction of feed and the type of cage floor as well as its interaction to production performance in broiler chickens. This study will use 100 DOC (Day Old Chick) day old which consists of 90 major research and an additional 10 to see the state over crowded. The treatments consisted of two factors: The first factor restrictions on feeding consists of: (1) Without limiting the feed (ad libitum), (2) Restrictions feed 15%, and (3) skip a day (feeding hoses one day). The second factor is the type of cage floor consists of: (1) Floor-type wire cages (cage), and (2) Floor type cage litter. The result of this research showed that ad libitum, restricted feeding 15% and skip a day feeding were significantly (P £ 0.01) influence to final body weight, body weight gain, feed consumption kumulatif, and feed conversion. While type cages and interaction were no significantly (P ³ 0.05) on all variable production of broiler chicken.